Outpatient induction of labour in the UK: a survey of practice. (September 2016) - Sharp, Andrew N.; Stock, Sarah J.; Alfirevic, Zarko
Abstract: Objective: To identify the current UK use of outpatient procedures for cervical ripening prior to induction of labour. Study design: Postal survey of consultant led obstetric units within the United Kingdom. A questionnaire was sent by post to 210 NHS consultant led obstetric units within the UK. Units that provided outpatient induction of labour (OP IOL) were asked complete a series of questions defining their protocol for risk stratification and management. Results: The survey had a 78% response rate. 17.6% of units stated that they currently or soon will provide OP IOL. All units were willing to provide OP IOL for post-dates singleton pregnancies and none provided this service for women with a previous caesarean or multiple pregnancy. 96% of inductions were initiated in a hospital setting prior to discharge home. 84% of units used Propess ® to initiate OP IOL and 96% had a fetal assessment with CTG. Only 40% of units had a clear mechanism for assessment once the woman had gone home. 72% of units performed regular audit of their practice. Conclusions: We suggest that robust comparative research within a UK context is urgently required to establish the safety and cost effectiveness of outpatient induction of labour before this technique becomes fully embedded in clinical care without an adequate evidence base.